2021
DOI: 10.1002/jcla.24197
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0000437 upregulates and promotes disease progression in rheumatic valvular heart disease

Abstract: Background: Currently, the diagnosis and outcome of rheumatic valvular heart disease (RVHD) are less than ideal, and there are no accurate biomarkers. Circular RNA (circRNA) might participate in the occurrence and development of RVHD. Materials and methods:We use circRNA microarray to filter out the target has_circ_0000437. qRT-PCR was used to measure the expression levels of hsa_ circ_0000437 in RVHD plasma samples. We assessed the diagnostic value of hsa_ circ_0000437 in RVHD. Cell function in vitro experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Total RNA extraction using the TRIzol LS reagent (Invitrogen) and reverse transcription were performed as previously described. 10 ABI 7500 System (Applied Biosystems, USA). GAPD H was used as the reference gene.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Total RNA extraction using the TRIzol LS reagent (Invitrogen) and reverse transcription were performed as previously described. 10 ABI 7500 System (Applied Biosystems, USA). GAPD H was used as the reference gene.…”
Section: Methodsmentioning
confidence: 99%
“…Data analysis was done using R software limma package. The circRNA array data were as previously described 10 . Differentially expressed circRNAs changes were identified with a fold change of >2.0 and p ‐value <0.05 as significant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro experiments showed that hsa_circ_0000437 promoted proliferation and migration but inhibited apoptosis in RVHD cells. 20 There is abnormal expression of circRNAs in patients with valvular heart disease complicated with atrial fibrillation. Investigators studied expression profiles of circRNAs, laying the foundation for future circRNA‐related research.…”
Section: Discussionmentioning
confidence: 99%